THE ROLE OF ACCOUNTING ACCOUNTING IN CONTROLLING QUALITY COSTS AND IMPROVING THE FINANCIAL PERFORMANCE OF IRAQI PHARMACEUTICAL COMPANIES (CASE STUDY) - Haider Tawfeeq Khalil, Hussein Ali Hisab, Adnan Askar Alwan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study here aimed at identifying that role of accounting control with quality costs (prevention costs, evaluation costs, internal failure costs, and external failure costs) in improving the financial performance of human drug manufacturers in Iraq. To achieve these goals, the research study has researchers designed two questionnaires. The first questionnaire was directed to both production and quality managers and included (25) paragraphs. And the second one was devoted to financial managers and accountants, and included (10) paragraphs in order to collect that initial information from the study sample. In light of that, the data was collected and analyzed and the hypotheses were tested using this SPSS statistical package. Which may consist of the study sample of (55) financial managers andaccountants.